Numerical Solutions on Mixed Convection Boundary Layer and Heat Transfer of Jeffrey Fluid over a Horizontal Circular Cylinder by using Keller-box Method - Syazwani, Mohd Zokri; Nur Syamilah, Arifin; Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Abdul Rahman, Mohd Kasim; Nurul Farahain, Mohammad (Universiti Malaysia Pahang, 2016)
This article discusses the numerical solutions on the problem of mixed convection boundary layer and heat transfer of Jeffrey fluid which passing over a horizontal circular cylinder. The governing boundary layer equations are first transformed into a system of non-dimensional equations using the non-dimensional variables, and then into non-similar equations before solving numerically using an implicit finite-difference scheme known as Keller-box method. Numerical solutions are obtained for the velocity and temperature profiles as well as the reduced Nusselt number and skin friction coefficient for various values of mixed convection parameter and Prandtl number, respectively.